1995
DOI: 10.1002/aja.1002030205
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the helix‐loop‐helix gene Id3 during murine embryonic development

Abstract: The family of dominant-negative helix-loop-helix (dnHLH) transcriptional modulators consists of four mammalian genes known to date: Idl, Id2, Id3 (Id3 was formerly designated HLH462 or HEIR1 or HLHlRBl), and Id4. We have performed a detailed study of Id3 expression in mouse embryos in order to gain insight into the possible developmental control functions of this gene and to compare its expression to that of other mammalian dnHLH genes. Employing RNA in situ hybridization on sectioned mouse embryos of gestatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 41 publications
(60 reference statements)
1
36
0
Order By: Relevance
“…Among the four Id proteins identified to date, expression patterns of Id1 and Id3 (in proliferating neural precursors in the ventricular zone) in the developing brain are quite similar (40)(41)(42)(43). BMP receptors are also expressed in cells located in the ventricular zone at a developmental stage when Id expression is observed (14).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Among the four Id proteins identified to date, expression patterns of Id1 and Id3 (in proliferating neural precursors in the ventricular zone) in the developing brain are quite similar (40)(41)(42)(43). BMP receptors are also expressed in cells located in the ventricular zone at a developmental stage when Id expression is observed (14).…”
Section: Discussionmentioning
confidence: 97%
“…In this regard, we observed that BMP2-induced expression of these two genes in cultured neuroepithelial cells was transient (reaching a peak level at 1 h and returning to the basal level within 24 h after BMP2 stimulation; unpublished data). In addition, expression of Id1 and Id3 is not observed in the brain at a late stage of development when GFAP-positive astrocytes are detected (40)(41)(42)(43). It should be noted that retrovirus-mediated expression of Id1 in cerebral cortex of embryonic or postnatal mouse leads to suppression of neurogenesis and induction of gliogenesis, as judged by cellular morphology, although the expression of glial marker proteins, such as GFAP, was not examined (44).…”
Section: Discussionmentioning
confidence: 99%
“…Id proteins are expressed in developing retina (Dickmeis et al, 2002;Jen et al, 1997;Zhang et al, 1995). Id1-4 are expressed in the developing mouse retina (Duncan et al, 1992;Ellmeier and Weith, 1995;Jen et al, 1997) and one homolog in the developing chicken retina (Helms et al, 1994). The expression of Pea3 may be regulated by autoinhibition, the presence of a coactivator or inhibitor, or some combination of the three.…”
Section: Discussionmentioning
confidence: 99%
“…Sox10 is another transcription factor that inhibits differentiation and maintains stem cell potential (Kim et al 2003). In addition, Id genes are known to affect proliferation of neuroepithelial cells and undifferentiated brain regions during central nervous system development (Evans and O'Brien 1993;Ellmeier and Weith 1995;Jen et al 1997). Id2 has been shown to enhance cell proliferation and interact with the retinoblastoma (Rb) proteins, mediating cell cycle progression by Myc (Iavarone et al 1994;Lasorella et al 1996Lasorella et al , 2000Toma et al 2000;Yokota and Mori 2002).…”
Section: Id3 Is An Essential Early Regulator Of Neural Crest Formationmentioning
confidence: 99%